“Newborn”: Komposisi Musik Programatik Bernuansa Jawa Dalam Kajian Practice-Based Research - Yota Hupekoos Ismono; Agastya Rama Listya (Journal of Music Science, Technology, and Industry, 2026)
Purpose: Yotaland is a programmatic composition with an ethnic nuance in a Western music format, consists of four movements that incorporate musical idioms from various Indonesian ethnicities. i.e., Javanese, Maluku, Balinese, and Batak. The purpose of this research is to analyze the first movement, which adopts Javanese ethnic elements. Method: This research employs a descriptive qualitative method with a practice-based research approach. Data collection is carried out through two types of sources, namely primary data and secondary data. Result and Discussion: The first movement, which is analyzed in depth, represents Javanese idiom through the Sinom song form, characterized by theme, repetition, improvisation, and transformation of various orchestration techniques, as well as changes in time signature. Implication: This research emphasizes that the exploration of local cultural identity can be achieved through contemporary musical media without losing its original aesthetic values and cultural meaning.